Audit Tata Kelola Teknologi Informasi pada Dinas Komunikasi dan Informatika (DISKOMINFO) Kota Probolinggo Menggunakan Kerangka Kerja COBIT 4.1 Domain Plan and Organise dan Acquire and Implement - Liliandara Wahyu Imami; Suprapto Suprapto; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Dinas Komunikasi dan Informatika (DISKOMINFO) Kota Probolinggo is an agency that responsible for communication, informatics, statistics, and encryption within the existing government environment. The existence of IT governance can provide assurance that the utilization of information technology in line with organizational business goals. Based on the results of the interviews found several problems in the management of IT governance such as the absence of SOPs, lack of understanding of human resources related to their respective tasks, and installation of infrastructure that is not in accordance with the Master Plan that has been planned. Therefore, audit to measure how far the Maturity Level and know the possibility of deviations from planned IT Governance. COBIT 4.1 is an appropriate framework for knowing the Maturity Level of information technology governance. The domains used are Plan and Organize and Acquire and Implement. This research is to get the result of evaluation based on maturity level and produce recommendation from result of evaluation. The result of the maturity level on the Plan and Organize domain is 1.9 and the Acquire and Implement domain is 1.28. Recommendations are used to improve the value of Maturity Level to improve the existing IT governance in DISKOMINFO Kota Probolinggo.